Get rid of unanimity: The superiority of majority rule with veto power - Laurent Bouton; Aniol Llorente-Saguer; Frédéric Malherbe (Queen Mary University of London, School of Economics and Finance, 2014)
A group of agents wants to reform the status quo if and only if this is Pareto improving. Agents have private information and may have common or private objectives, which creates a tension between information aggregation and minority protection. We analyze a simple voting system - majority rule with veto power (Veto) - that essentially resolves this tension, for it combines the advantageous properties of both majority and unanimity rules. We argue that our results shed new light on the evolution of voting rules in the EU institutions and could help to inform debates about policy reforms in cases such as juries in the US.
Keywords: D70; 330; Unanimity rule; Veto power; Information aggregation; Pareto criterion; Constructive abstention; Abstimmungsregel; Veto; Pareto-Optimum; Theorie; EU-Staaten; Welt